PREPROCESSING OF HOPKINSON BAR EXPERIMENT DATA: FILTER ANALYSIS - Marcel Adorna; Jan Falta; Tomáš Fíla; Petr Zlámal (Acta Polytechnica CTU Proceedings)
This work presents a data preprocessing procedure for signal acquired during high strain-rate loading using a custom Split Hopkinson Pressure Bar (SHPB). Before the evaluation of the experimental data, preprocessing of the measured signals including application of suitable digital or analog filter needs to be performed. Our department mainly focuses on measurements performed on advanced materials (e.g. materials with predefined structures or hybrid foams). For such measurements, it is essential to perform data preprocessing and apply suitable filter, to be able to appropriately determine deformation pulses on the measuring bars. This paper focuses foremost on spectral analysis of the measured signals, and design of optimal method of data filtering. Data from several different SHPB experiments were processed and results of different filtering methods are shown in this paper. Parameters of the best performing filter were optimized and shown to be universal for wide range of SHPB measurements.